A comparison of Sorghum Stover based complete feed blocks with a conventional feeding practice in a peri urban dairy - Samireddypalle, A.; Khan, A.A.; Ravi, D.; Reddy, J.; Blümmel, Michael (2010)
Sorghum stover is a major constituent in dairy feeding in and around Hyderabad, transported over long distances and traded and priced according to perceived stover fodder quality by specialized fodder traders. The work presented here assessed the economics of three feeding regimes: 1) a complete feed block consisting of about 50% of a premium sorghum stover (T1), 2) a complete feed block consisting of about 50% of a low cost sorghum stover (T2); and 3) a conventional feeding regime based on farmmixed concentrate and green fodder (T3). At a commercial dairy farm seven Murrah buffaloes each were allotted to any of the three treatments recording daily feed intake, milk yield and milk fat content. Dry matter, protein and metabolisable energy intake were highest (P<0.05) in T1 followed by T2 and T3. Average daily milk yield were 8.6, 7.9 and 7.0 liter in T3, T1 and T2, respectively (P=0.20). Feeding costs relative to sales from milk were 40% (P<0.05) in T3 compared to 69% in T1 and 67% in T2. ME intakes relative to estimated ME requirements were 151% in T1, 130% in T2 and 93% in T3, respectively.